Pendidikan dan Problem Kemiskinan (Sebuah Kajian pada Pandangan para Mufassir dan Teolog) - Rafiudin (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2018)
Education is used as a tool to shape change for the better in various aspects, including in terms of the economy. Education should lead to the welfare of the nation and Muslims, along with the high level of education of the nation's leaders and government officials. But, of the many scholars who have managed to reach the level of higher education to the highest level, but welfare has not arrived. This is exacerbated by the presence of corrupt behavior from highly educated leaders as if adding to the pessimistic space that education can bring to the welfare of the nation and Muslims in Indonesia. Cases of corruption are rampant in the midst of a nation that is predominantly Muslim and has a high degree of education. The following literature study tries to discuss corruption in terms of the thoughts of commentators and theologians. The study of corruption shows that so heavy is the burden of sin or error for corrupt behavior, but in fact, it is still considered light even by people who understand correctly the adverse effects of corruption both for themselves and for the benefit of the Indonesian people and nation, primarily will perpetuate the people to be poor.